Synthesis and Characterization of Zinc Nanoparticles for Antibacterial Coating Applications in Laboratory Textiles - Lawand, Sura Sameer Saeed; Khanyab, Mawj Malik Younis (Central Asian Journal of Medical and Natural Science, 2025)
Zinc nanoparticles (Zn NPs) were successfully synthesized using a chemical precipitation technique to investigate their structural, morphological, and antibacterial characteristics. Sodium hydroxide was used as a catalyst to enhance solubility and control nanoparticle formation. The resulting Zn NPs were characterized by X-ray diffraction (XRD) and scanning electron microscopy (SEM). XRD analysis confirmed that the nanoparticles possess a polycrystalline structure composed mainly of hexagonal wurtzite and orthorhombic phases. SEM images revealed cylindrical and aggregated morphologies with particle sizes between 24 and 70 nm. The antibacterial performance of Zn NPs was tested against Escherichia coli (Gram-negative) and Staphylococcus aureus (Gram-positive), where significant inhibition zones were observed. These findings demonstrate the potential of Zn nanoparticles as an efficient, biocompatible, and low-cost antibacterial coating material suitable for laboratory textiles and biomedical applications.